Impact of global cotton markets on rural poverty in Benin - Minot, Nicholas; Daniels, Lisa (International Food Policy Research Institute, 2002)
World cotton prices have fallen by about 40 percent over the last two years, focusing attention on the effect of subsidies for cotton growers in depressing prices. This paper combines farm survey data from Benin with assumptions about the decline in farm-level prices to estimate the direct and indirect effects of cotton price reductions on rural income and poverty in Benin. The results indicate that there is a strong link between cotton prices and rural welfare in Benin. A 40 percent reduction in farm-level prices of cotton results in an increase in rural poverty of 8 percentage points in the short-run and 6-7 percentage points in the long run. Based on the estimated marginal propensity to consume tradable goods, the consumption multiplier is in the range of 3.3, meaning that one dollar of reduced spending by cotton growers results in a contraction of 3.3 dollars in overall demand. Finally, econometric analysis of the determinants of the demand for hired agricultural labor suggests that falling cotton prices will not greatly reduce labor demand since the labor intensity of cotton is similar to that of competing crops in Benin. Overall, the study highlights the link between rising subsidies for cotton growers in the U.S. and rural poverty in cotton exporting countries such as Benin.